The Effect of the CIRC and Learning Motivation on Reading Comprehension Skills for Junior High School Students - Mayang Sari Hasibuan; Afnita Afnita (STAI Hubbulwathan Duri, 2022)
This study aimed to analyze how the CIRC learning model and learning motivation affected students' reading comprehension abilities. This study uses a 2x2 factorial design and a quasi-experimental methodology. A reading comprehension test and a questionnaire about learning motivation were employed in the study. A total of 24 people from each group were used to create the research sample. Data analysis was done descriptively. The results showed that CIRC influenced students' reading comprehension results. The experimental class (CIRC) students had a greater reading comprehension level than those in the control group (conventional). The reading comprehension skills of students with high learning motivation (CIRC) differ significantly from those of pupils with low learning motivation (traditional). The reading comprehension skills of students with low learning motivation (CIRC) differ considerably from those of pupils with high levels of stimulation (conventional). The CIRC model interacts with learning motivation to influence students' reading comprehension skills. Students with high reading interest (CIRC) can improve their ability to read and understand explanatory texts and vice versa.